2010
DOI: 10.1177/0956797610361446
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Taxes and Subsidies on Energy Purchased in an Experimental Purchasing Study

Abstract: There is limited research on how taxes and subsidies would influence the energy and nutritional quality of food purchases. Using an experimental analogue purchasing task, we examined the effects of increasing the price of high-calorie-for-nutrient foods or reducing the price of low-calorie-for-nutrient foods by 12.5% and 25% on mothers' purchases of 68 common foods and drinks. Taxing less healthy foods with low nutrient density reduced energy (caloric) intake, while reducing the proportion of fat and increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
157
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(169 citation statements)
references
References 22 publications
8
157
2
1
Order By: Relevance
“…There is limited research on the influence of taxes and subsidies on nutritional quality of food purchases. Evidence suggests stronger support for taxes than for subsidies as a means of reducing consumption of less healthy foods (40) . It has been estimated that a 10 % increase in soft drink prices would reduce consumption by 8-10 % (43) .…”
Section: Discussionmentioning
confidence: 99%
“…There is limited research on the influence of taxes and subsidies on nutritional quality of food purchases. Evidence suggests stronger support for taxes than for subsidies as a means of reducing consumption of less healthy foods (40) . It has been estimated that a 10 % increase in soft drink prices would reduce consumption by 8-10 % (43) .…”
Section: Discussionmentioning
confidence: 99%
“…Healthy food subsidies, on the other hand, increased the total amount of fat, protein and carbohydrates bought. The participants spent the money saved to buy junk food 9 .…”
Section: Healthy Influencesmentioning
confidence: 99%
“…Also, they found that reducing prices of fruits and vegetables with 50 per cent in school canteens lead to a twofold increase in vegetable and four-fold increase in fruit purchases [40]. Other experimental studies are the work by Epstein and colleagues who conducted a study on several pricing schemes in a laboratory supermarket [42], the work by Nederkoorn and colleagues on a high caloric tax in a web-based supermarket [43], and the work by Giesen and colleagues on taxing high caloric university lunch menus [44]. All these studies revealed significant effects of the price changes.…”
Section: Evidence On the Effectiveness Of Food Pricing Strategiesmentioning
confidence: 99%